Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Kabola Kabupaten Alor - Alvonso Fanisius Gorang; Hermayanti Hermayanti; Theresia Lounggina Luisa Peny; Mesak Yamres Awang (Peneliti.net, 2022)
Performance is an achievement or level of success achieved by a person (individual) or an organization in carrying out work in a certain period. This study aims to determine the effect of work motivation, work discipline, and work environment on the performance of employees of the Kabola District office, Alor Regency. This type of research is quantitative research with data collection techniques namely observation, interviews, and documentation studies while data analysis is significant with the t-test and F-test. The results of this study indicate that: Partially the work motivation variable has a significant effect on employee performance with a significance value of the t-test of 0.032. Partially the Work Discipline Variable has a significant effect on employee performance with a significance value of the t-test of 0.034. Partially, the Work Environment Variable has no significant effect on employee performance with a significance value of the t-test of 0.220. Simultaneously the variables Work Motivation (X1), Work Discipline (X2), and Work Environment (X3) have a significant effect on employee performance variables (Y) with a significance value of the F test of 0.000.